Antibacterial mechanism of bacteriocin from Lactobacillus plantarum YP36 based on proteomics technology - WANG Ting, LAI Huanhuan, ZHAO Wei, CUI Meilin, ZHANG Xiuhong (Zhongguo niangzao)
In order to understand the antibacterial mechanism of bacteriocin from Lactobacillus plantarum YP36, the differential expression proteins of L. plantarum SL32-2 before and after bacteriocin treatment were analyzed by high performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) combined with label-free quantitative proteomics technique, and the metabolic function of the differential proteins were analyzed. The results showed that 1 999 and 2 005 proteins were identified in the fermentation broth of L. plantarum SL32-2 before and after bacteriocin treatment respectively, 15 and 59 proteins were significantly up-regulated and down-regulated, 26 proteins were disappeared, and 33 proteins were induced to expression. Among the identified proteins, enzymes accounted for the largest proportion, followed by transporters. Gene Ontology (GO) enrichment analysis showed that there were 99 functional items of significantly differentially expressed proteins, which mainly focused on peptidoglycan catabolism, cell wall macromolecular catabolism, carbohydrate metabolism, pyrimidine nucleotide metabolism and biosynthesis. The Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis showed that the differential proteins involved 53 pathways including starch and sucrose metabolism, alanine, aspartate and glutamate metabolism, cofactor biosynthesis and pyrimidine metabolism.